Antibacterial soft skin-friendly fabric and preparation method thereof

By using hydrophobically modified chitosan, modal fiber and polylactic acid in the fabric, the problem of reducing the antibacterial effect of chitosan in humid environments is solved, and the fabric has good antibacterial, softness and skin-friendliness in high humidity environments are achieved.

CN118480893BActive Publication Date: 2025-03-07GUANGDONG QIYUE FUTURE TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410550211.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-06
Publication Date
2025-03-07
Estimated Expiration
2044-05-06

AI Technical Summary

Technical Problem

Chitosan has greatly reduced its antibacterial effect in humid environments, resulting in mold breeding in high humidity environments and black spots.

Method used

Antibacterial soft and skin-friendly fabrics are prepared by hydrophobically modified chitosan, modal fiber, polylactic acid, calcium carbonate powder, coupling agent and polyethylene wax. The water absorption is reduced by hydrophobically modified chitosan, and polylactic acid and modal fibers improve softness and antibacterial properties.

Benefits of technology

Maintain good antibacterial effect in high humidity environments, prevent mold from growing, improve the softness and skin-friendliness of the fabric, and enhance the comfort of use.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004824045420000051
    Figure BDA0004824045420000051
  • Figure BDA0004824045420000061
    Figure BDA0004824045420000061
  • Figure BDA0004824045420000081
    Figure BDA0004824045420000081
Patent Text Reader

Abstract

The present application relates to the field of fabric processing technology, and in particular to an antibacterial soft skin-friendly fabric and a preparation method thereof, which is prepared by the following raw materials in weight percentage: 60-65 parts of modal fiber, 30-35 parts of polylactic acid, 3-6 parts of hydrophobically modified chitosan, 1-3 parts of coupling agent, 5-10 parts of calcium carbonate powder and 2-5 parts of polyethylene wax. The antibacterial soft skin-friendly fabric prepared by adopting the above formula has good softness and skin-friendliness, and also has good antibacterial effect in a high humidity environment, and will not produce mildew spots.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of fabric processing, and in particular to an antibacterial, soft, skin-friendly fabric and a preparation method thereof. Background Art

[0002] Antibacterial fabric is a kind of fabric that can inhibit the growth of bacteria. Antibacterial fabric is often used in home clothes, underwear and bedding. One of the preparation methods of antibacterial fabric is to fully mix the fabric antibacterial agent, other additives and polymer resin, and then prepare it into antibacterial fiber by melt spinning, and then weave the antibacterial fiber into antibacterial fabric. Among them, the main fabric antibacterial agent is chitosan antibacterial agent, which is extracted from the shells of marine organisms such as shrimps and crabs. It is safe and non-toxic and can inhibit the growth and reproduction of many kinds of molds.

[0003] However, the antibacterial effect of chitosan is easily affected by the environment. In a high-humidity environment, the antibacterial effect is greatly reduced, especially in the south during the return of the south wind. Doors and windows basically cannot be opened during the return of the south wind. The humid environment plus poor ventilation can cause a large number of mold to grow on the fabric in just a few days, resulting in black spots, so improvement is needed. Summary of the invention

[0004] In order to solve the problem that the antibacterial effect of chitosan is greatly reduced in a humid environment, the present application provides an antibacterial, soft, skin-friendly fabric and a preparation method thereof.

[0005] An antibacterial, soft and skin-friendly fabric adopts the following technical solution:

[0006] An antibacterial, soft and skin-friendly fabric is prepared by including the following raw materials in percentage by weight:

[0007] Modal fiber 60-65 parts

[0008] Polylactic acid 30-35 parts

[0009] 3-6 parts of hydrophobically modified chitosan

[0010] Calcium carbonate powder 5-10 parts

[0011] Coupling agent 1-3 parts

[0012] 2-5 parts of polyethylene wax.

[0013] By adopting the above technical solution, the prepared antibacterial soft skin-friendly fabric has good softness and skin-friendliness, and also has good antibacterial effect in a high humidity environment without producing mildew spots.

[0014] Hydrophobic chitosan can reduce the water absorption of chitosan and reduce the impact of environmental humidity on the antibacterial effect of chitosan. Chitosan is a natural high molecular weight polysaccharide with good hygroscopicity, so it easily absorbs moisture in a humid environment. When chitosan absorbs moisture, the interaction between its molecular chains will weaken, causing the molecular structure to become loose, thus affecting its antibacterial properties. Hydrophobic chitosan has hydrophobic groups that prevent moisture from entering the interior of chitosan. Therefore, in a humid environment, it will not affect the structure and antibacterial effect of chitosan.

[0015] Modal fiber has good softness and hygroscopicity. It can improve the softness of fabrics when used to prepare fabrics. However, in a humid environment, modal absorbs more water, which easily causes bacteria to grow on fabrics. Therefore, in this application, polylactic acid and hydrophobic chitosan are added to prevent modal fiber from growing bacteria in a humid environment. Among them, polylactic acid has good skin affinity and is not easy to breed bacteria. Hydrophobic chitosan is not easy to absorb water and can also play an antibacterial role in a humid environment. Therefore, modal fiber and polylactic acid are used in this application. In this application, hydrophobic chitosan, modal fiber and polylactic acid are used in combination to ensure that the fabric has good antibacterial properties, breathability and skin affinity in a high humidity environment. When used in the return of the south, no bacteria will be produced and black spots will appear.

[0016] Modal fiber has good moisture absorption. When the south wind returns, the fabric feels sticky, which greatly increases the discomfort of using clothes and bedding. In this application, calcium carbonate powder is added to reduce the stickiness of the fabric, making the fabric smooth, dry and skin-friendly, and improving the comfort of use.

[0017] The surface properties of polylactic acid and hydrophobic chitosan are different, and they are easy to mix unevenly. Polyethylene wax is a non-water-absorbent substance. By adding polyethylene wax, the mixing uniformity of the two can be improved. At the same time, it will not introduce too much moisture into the fabric, increase the moisture height of the fabric, and affect the antibacterial property of the fabric.

[0018] The coupling agent is used to enhance the binding force between hydrophobic chitosan, calcium carbonate and polylactic acid, and further improve the antibacterial effect of the fabric.

[0019] Preferably, the hydrophobic chitosan is prepared by the following method:

[0020] A: mixing the aromatic ketone with a water-insoluble organic solvent to obtain a mixed solution;

[0021] B: Dissolve chitosan in acetic acid until the chitosan is dissolved, heat to 40-50°C, add the mixed solution, add an acid catalyst during stirring, continue stirring for 5-8 hours, then add sodium borohydride, stir for 1-2 hours to obtain a primary product;

[0022] C: Place the primary product in 20-25°C water, stir, filter to obtain a solid, rinse, and dry to obtain hydrophobic chitosan.

[0023] By adopting the above technical solution, the hydrophobic chitosan obtained has good hydrophobicity and can maintain good antibacterial effect in a humid environment.

[0024] Aromatic ketones have low affinity for water. In the present application, chitosan is reacted with aromatic ketones to change the molecular structure of chitosan, making it less likely to absorb water, thereby achieving a hydrophobic effect without affecting the antibacterial effect of chitosan.

[0025] In step A, the aromatic ketone is dissolved in a water-insoluble organic solvent to dilute the aromatic ketone, which is beneficial for the reaction between the aromatic ketone and chitosan.

[0026] In step B, chitosan is dissolved in acetic acid, and the acidic catalyst is used to improve the reaction efficiency of chitosan and aromatic ketone and the reaction rate. Then, sodium borohydride is added for reduction, so that the aromatic ketone is introduced into chitosan to achieve the purpose of hydrophobicity.

[0027] Adding ice water in step C is beneficial to the precipitation of solid.

[0028] Preferably, the molar ratio of the aromatic ketone to the chitosan is 1:(1.1-1.3).

[0029] Preferably, the molar ratio of the aromatic ketone to the sodium borohydride is 1:(1.3-1.5).

[0030] By adopting the above technical solution, the aromatic ketone can fully react with chitosan, the residual aromatic ketone is reduced, and the purity of the hydrophobic chitosan is improved.

[0031] Preferably, the acidic catalyst is hydrochloric acid or sulfuric acid.

[0032] By adopting the above technical solution, the reaction efficiency of chitosan and aromatic ketone is further improved, the reaction time is shortened, and the productivity is improved.

[0033] Preferably, the modal fiber needs to be pretreated before use, and the pretreatment steps are as follows:

[0034] The modal fiber is immersed in a solution containing a hydrophobic organic silane coupling agent, taken out, and dried to obtain the pretreated modal fiber.

[0035] By adopting the above technical solution, a small amount of hydrophobic groups are grafted on the surface of modal fiber, which reduces the moisture absorbed by the fabric in the air and reduces the growth of bacteria. The high humidity in the return of south wind makes the fabric wet, which makes it easier for bacteria to grow. In this regard, by reacting modal fiber with hydrophobic organosilane, a small amount of hydrophobic groups are grafted on the surface of modal fiber, which appropriately improves the hydrophobicity of modal fiber, reduces the moisture absorbed by the fabric, and further reduces the growth of bacteria.

[0036] Preferably, the hydrophobic silane coupling agent includes one of vinyltrimethoxysilane, phenyltrimethoxysilane, perfluorosilane or a linear silane having more than 15 carbon atoms.

[0037] By adopting the hydrophobic organosilane, the hydrophobicity of the modal fiber is further improved, the absorption of moisture in the air by the modal fiber is reduced, the dryness of the fabric is increased, and the growth of bacteria is reduced.

[0038] Preferably, the mass fraction of the solution containing the hydrophobic organosilane coupling agent is 2-5%.

[0039] By adopting the above technical solution, the mass fraction of the solution containing hydrophobic organic silane coupling agent is optimized, so that the surface of modal fiber contains an appropriate amount of hydrophobic groups, which reduces the absorption of moisture in the air, increases the dryness of the fabric, and reduces bacterial growth.

[0040] Preferably, the weight average molecular weight of the polylactic acid is 70,000-150,000.

[0041] By adopting the above technical scheme, the weight average molecular weight of polylactic acid is optimized, so that the polylactic acid fiber has good mechanical properties and softness. If the weight average molecular weight of polylactic acid is too high, the hardness of the polylactic acid fiber will increase and the softness will decrease; if the weight average molecular weight of polylactic acid is too small, the strength of the polylactic acid fiber will decrease and it will be easy to break, affecting its use.

[0042] Preferably, the antibacterial, soft and skin-friendly fabric further comprises 4-8 parts by weight of a composite breathable filler, each part of the composite breathable filler being obtained by mixing a nano-scale porous inorganic substance and a dispersant in a weight ratio of 5:(1-2).

[0043] By adopting the above technical solution, the air permeability of the fabric is further improved, and the amount of water remaining in the fabric for a long time is reduced, thereby reducing the growth of bacteria. The porous structure of the nano-porous inorganic material can pass through air, which can increase the air permeability of the polylactic acid fiber and increase the air permeability of the fabric. The dispersant increases the fluidity of the porous inorganic material, improves the uniformity of the nano-porous inorganic material in the polylactic acid, and improves the air permeability effect. At the same time, the nano-porous inorganic material has a relatively delicate feel, which can further improve the skin-friendly feel of the fabric.

[0044] Preferably, the nano-scale porous inorganic material is nano-porous ceramic powder, nano-porous carbon powder, porous nano-boehmite, porous nano-aluminum hydroxide, porous nano-zinc oxide, nano-zeolite and the like.

[0045] Preferably, the dispersant is one or more of sodium polyacrylate, polyvinyl alcohol, polyethylene glycol or paraffin.

[0046] In a second aspect, the present application provides a method for preparing an antibacterial, soft and skin-friendly fabric, using the following technical solution:

[0047] A method for preparing an antibacterial, soft and skin-friendly fabric comprises the following preparation steps:

[0048] S1. According to the weight percentage, polylactic acid, hydrophobic chitosan, calcium carbonate powder, coupling agent and polyethylene wax are first mixed, and the mixture is put into a spinning box for spinning at a spinning temperature of 200-230° C. and a spinning winding speed of 1000-2000 m / min, and then drafted at a drafting temperature of 180-190° C. and a drafting speed of 1000-1500 m / min to obtain polylactic acid fiber;

[0049] S2. Blending the polylactic acid fiber with the modal fiber to obtain an antibacterial, soft and skin-friendly fabric.

[0050] By adopting the above technical solution, the prepared fabric has good antibacterial effect in a humid environment, and also has good air permeability and skin-friendliness.

[0051] In step S1, polylactic acid, hydrophobic chitosan, a coupling agent, calcium carbonate and polyethylene wax are spun so that the hydrophobic chitosan and calcium carbonate are evenly dispersed in the polylactic acid fiber, which is beneficial to improving the antibacterial effect of the polylactic acid fiber.

[0052] Hydrophobic chitosan cannot be directly added to modal fibers. In the present application, the hydrophobic chitosan is first evenly dispersed in polylactic acid to form polylactic acid fibers, and then the polylactic acid fibers are blended with the modal fibers. That is, in S2, the polylactic acid fibers and the modal fibers are blended so that the polylactic acid fibers and the modal fibers are fully and evenly mixed, so that the hydrophobic chitosan can be further evenly distributed in every corner of the fabric, thereby improving the antibacterial effect of the fabric in a high humidity environment.

[0053] In summary, this application has the following beneficial effects:

[0054] 1. By preparing fabrics with modal fiber, polylactic acid, hydrophobically modified chitosan, coupling agent, calcium carbonate powder and polyethylene wax, the antibacterial property, softness and skin affinity of the fabrics can be greatly improved, and the comfort of the fabrics during the return of the south wind can be improved.

[0055] 2. The present application obtains hydrophobic chitosan by reacting aromatic ketone and chitosan under the action of an acid catalyst and then reducing it with sodium borohydride, thereby reducing the water absorption of chitosan and allowing chitosan to exert an antibacterial effect even in a high humidity environment. DETAILED DESCRIPTION

[0056] Example

[0057] Example 1

[0058] An antibacterial, soft and skin-friendly fabric is prepared by the following method:

[0059] S1, firstly mix 300g of polylactic acid, 30g of hydrophobic chitosan, 10g of coupling agent (titanate coupling agent), calcium carbonate powder and 20g of polyethylene wax, put them into a spinning box for spinning, the spinning temperature is 200°C, the spinning winding speed is 1000m / min, and then stretching, the stretching temperature is 180°C, and the stretching speed is 1000m / min, to obtain polylactic acid fiber;

[0060] S2. Blending the polylactic acid fiber with the modal fiber to obtain an antibacterial, soft and skin-friendly fabric.

[0061] The weight average molecular weight of polylactic acid is 70,000.

[0062] The hydrophobic chitosan is N-ethyl chitosan.

[0063] The molecular weight of polyethylene wax is 2000.

[0064] Example 2

[0065] An antibacterial, soft and skin-friendly fabric is prepared by the following method:

[0066] S1, first mix 650g of polylactic acid, 60g of hydrophobic chitosan, 30g of coupling agent (titanate coupling agent), calcium carbonate powder and 50g of polyethylene wax, put them into a spinning box for spinning, the spinning temperature is 230°C, the spinning winding speed is 2000m / min, and then stretching, the stretching temperature is 190°C, and the stretching speed is 1500m / min to obtain polylactic acid fiber;

[0067] S2. Blending the polylactic acid fiber with the modal fiber to obtain an antibacterial, soft and skin-friendly fabric.

[0068] The weight average molecular weight of polylactic acid is 150,000.

[0069] The hydrophobic chitosan is N-ethyl chitosan.

[0070] The molecular weight of polyethylene wax is 5000.

[0071] Example 3

[0072] An antibacterial, soft and skin-friendly fabric. The difference between this embodiment and embodiment 1 is that the hydrophobic chitosan is prepared by the following method:

[0073] A: 0.73 g of aromatic ketone (acetophenone) and 5 g of water-insoluble organic solvent (petroleum ether) were mixed to obtain a mixed solution;

[0074] B: Dissolve 80g of chitosan in 100g of acetic acid until the chitosan is dissolved, heat to 40°C, add the mixture, add 0.1g of acidic catalyst (concentrated hydrochloric acid) during stirring, continue stirring for 5h, then add sodium borohydride, stir for 1h to obtain the primary product;

[0075] C: Place the primary product in 20°C water, stir, filter, obtain solid, rinse, and dry to obtain hydrophobic chitosan.

[0076] The difference between Example 4-5 and Example 3 is that some parameters for preparing hydrophobic chitosan are different, and the specific differences are shown in Table 1:

[0077] Table 1 Types, amounts and parameters of raw materials used to prepare hydrophobic chitosan in Examples 3-5

[0078]

[0079]

[0080] In Example 3, the molar ratio of aromatic ketone to chitosan is 1:1.1, and the molar ratio of aromatic ketone to sodium borohydride is 1:1.3.

[0081] In Example 4, the molar ratio of aromatic ketone to chitosan is 1:1.2, and the molar ratio of aromatic ketone to sodium borohydride is 1:1.4.

[0082] In Example 5, the molar ratio of aromatic ketone to chitosan is 1:1.3, and the molar ratio of aromatic ketone to sodium borohydride is 1:1.5.

[0083] Example 6

[0084] An antibacterial, soft, skin-friendly fabric. The difference between this embodiment and embodiment 3 is that the aromatic ketone is replaced by phenylacetaldehyde, and the other raw material types, amounts and experimental parameters are consistent with those of embodiment 3.

[0085] Example 7

[0086] An antibacterial, soft, skin-friendly fabric. The difference between this embodiment and embodiment 3 is that the aromatic ketone is replaced by acetic anhydride, and the other raw material types, amounts and experimental parameters are consistent with those of embodiment 3.

[0087] Example 8

[0088] An antibacterial, soft, skin-friendly fabric. The difference between this embodiment and embodiment 3 is that the molar ratio of 0.88 g of aromatic ketone to chitosan (80 g) is 1.1:1, and the types, amounts, and experimental parameters of other raw materials are consistent with those of embodiment 3.

[0089] Example 9

[0090] An antibacterial, soft and skin-friendly fabric. The difference between this embodiment and embodiment 1 is that the modal fiber needs to be pretreated before use. The pretreatment steps are as follows:

[0091] The modal fiber is immersed in a solution containing a hydrophobic organic silane coupling agent, taken out, and dried to obtain the pretreated modal fiber.

[0092] The hydrophobic organic silane coupling agent solution is prepared by mixing vinyl trimethoxy silane with ethanol to obtain a solution with a mass fraction of 5%.

[0093] Example 10

[0094] An antibacterial, soft and skin-friendly fabric. The difference between this embodiment and embodiment 1 is that the modal fiber needs to be pretreated before use. The pretreatment steps are as follows:

[0095] The modal fiber is immersed in a solution containing a hydrophobic organic silane coupling agent, taken out, and dried to obtain the pretreated modal fiber.

[0096] The hydrophobic organic silane coupling agent-containing solution is prepared by mixing heptadecafluorodecyltrimethoxysilane with ethanol to obtain a solution with a mass fraction of 2%.

[0097] Embodiment 11

[0098] An antibacterial, soft, skin-friendly fabric. The difference between this embodiment and embodiment 1 is that: in step S1, 40g of a composite breathable filler is further added. The composite breathable filler is obtained by mixing 33.3g of a nano-scale porous inorganic substance (porous ceramic powder) and 6.7g of a dispersant (polyvinyl alcohol) in a weight ratio of 5:1. The other raw material types, amounts, and experimental parameters are consistent with those in embodiment 1.

[0099] Example 12

[0100] An antibacterial, soft, skin-friendly fabric. The difference between this embodiment and embodiment 1 is that: in step S1, 80g of a composite breathable filler is also added. The composite breathable filler is obtained by mixing 57.1g of nano-scale porous inorganic matter (porous ceramic powder) and 22.9g of dispersant (paraffin) in a weight ratio of 5:2. The other raw material types, amounts and experimental parameters are consistent with those in embodiment 1.

[0101] Comparative Example

[0102] Comparative Example 1

[0103] The invention discloses an antibacterial, soft and skin-friendly fabric. The difference between this comparative example and Example 1 is that chitosan is used instead of hydrophobic chitosan, and the types, amounts and experimental parameters of other raw materials are consistent with those of Example 1.

[0104] Comparative Example 2

[0105] The invention discloses an antibacterial, soft and skin-friendly fabric. The difference between this comparative example and Example 1 is that cotton fiber is used instead of modal fiber, and the types, amounts and experimental parameters of other raw materials are consistent with those of Example 1.

[0106] Comparative Example 3

[0107] The invention discloses an antibacterial, soft and skin-friendly fabric. The difference between this comparative example and Example 1 is that polyacrylic acid is used instead of polylactic acid, and the types, amounts and experimental parameters of other raw materials are consistent with those of Example 1.

[0108] The molecular weight of polyacrylic acid is 20,000.

[0109] Comparative Example 4

[0110] The invention discloses an antibacterial, soft and skin-friendly fabric. The difference between this comparative example and Example 1 is that calcium carbonate powder is replaced with methyl cellulose, and the other raw material types, dosages and experimental parameters are consistent with those in Example 1.

[0111] Performance testing

[0112] The antibacterial, soft and skin-friendly fabrics prepared in Examples 1-12 and Comparative Examples 1-4 were subjected to antibacterial tests, softness tests and skin-friendly tests.

[0113] Detection method / test method

[0114] Antibacterial test: To simulate the environment of the return of south wind, the laboratory temperature was set at 30°C and the humidity was set at 90%. The antibacterial, soft and skin-friendly fabrics prepared in Examples 1-12 and Comparative Examples 1-4 were placed in the laboratory, and the time for the appearance of mold on each piece of fabric was observed. If no mold appeared after 240 hours, the test was discontinued.

[0115] Softness test: Tested by fabric style tester, Grade IV, Grade I has the best softness, Grade IV, Grade I has the best softness.

[0116] Skin-friendly property test: The antibacterial soft skin-friendly fabrics prepared in Examples 1-12 and Comparative Examples 1-4 were placed in a laboratory simulating the return of the south wind for 10 hours. 600 people were selected, including 200 people aged 10-20, 200 people aged 20-40, and 200 people aged 40-60. The antibacterial soft skin-friendly fabrics were touched in turn, and the number of people who thought the skin-friendly fabrics were good was recorded. The experimental data are shown in Table 2:

[0117] Table 2 Experimental data of Examples 1-12 and Comparative Examples 1-4

[0118]

[0119]

[0120] It can be seen from Examples 1-12 and Comparative Examples 1-4 in combination with Table 2 that in the present application, by preparing fabrics together with modal fiber, polylactic acid, hydrophobically modified chitosan, a coupling agent, calcium carbonate powder and polyethylene wax, the antibacterial performance, softness and skin-friendliness of the fabrics can be greatly improved, and the comfort of use of the fabrics during the return of the south wind can be improved.

[0121] Comparing Example 1 with Comparative Example 1, mold appeared in Comparative Example 1 within 25 hours in the mold test, and the number of people who felt skin-friendly in Comparative Example 1 in the skin-friendly test was even less than that in Example 1, indicating that the antibacterial properties and skin-friendly properties of the fabric can be greatly improved by using hydrophobic chitosan and other ingredients to prepare the fabric in the present application.

[0122] By comparing Example 1 with Comparative Example 2, mold appeared in Comparative Example 2 at 195h in the mold test, and the number of people who felt skin-friendly in Comparative Example 2 in the skin-friendly test was even less than that in Example 1, and the softness test grade was III, indicating that the fabric prepared with modal fiber in the present application can improve the antibacterial performance, softness and skin-friendlyness of the fabric.

[0123] Comparing Example 1 with Comparative Example 3, mold appeared in Comparative Example 3 at 182 hours in the mold test. In the skin-friendliness test, the number of people who felt skin-friendly in Comparative Example 3 was even less than that in Example 1. The softness test grade was III, indicating that the polylactic acid fiber prepared from polylactic acid in the present application can improve the antibacterial properties, softness and skin-friendliness of the fabric.

[0124] Comparing Example 1 with Comparative Example 4, mold appeared in Comparative Example 3 at 201h in the mold test, and the number of people who felt skin-friendly in Comparative Example 3 in the skin-friendly test was even less than that in Example 1, indicating that the use of calcium carbonate powder and other ingredients in the preparation of fabrics in this application can improve the antibacterial properties and skin-friendly properties of the fabrics.

[0125] Comparing Example 1 with Example 3, no mold appeared in Example 3 in the mold test, and the number of people who felt skin-friendly in Comparative Example 3 was slightly higher than that in Example 1 in the skin-friendly test;

[0126] Comparing Example 3 with Example 6-7, mold appeared in Example 6-7 at 217h and 198h respectively in the mold test, and the number of people who felt that Example 6-7 was skin-friendly in the skin-affinity test was less than 543. It can be seen that the hydrophobic chitosan obtained by reacting aromatic ketone with chitosan has better antibacterial effect and better skin affinity in a high humidity environment.

[0127] Comparing Example 3 with Example 8, in the skin-affinity test, the number of people who felt that the fabric in Example 8 was skin-affinity was even less than that in Example 3, indicating that the skin-affinity of the fabric can be improved by optimizing the dosage of aromatic ketone and chitosan.

[0128] Comparing Example 1 with Examples 9-10, in the mold test, mold appeared in Examples 6-7 at 236h and 237h respectively, and the softness test grade was I. In the skin-friendliness test, more people felt skin-friendly in Examples 6-7 than in Example 1, indicating that the antibacterial property, softness and skin-friendliness of the fabric can be improved by treating the modal fiber with hydrophobic organosilane.

[0129] Comparing Example 1 with Examples 11-12, mold appeared in Examples 11-12 at 239h and 237h respectively in the mold test, and in the skin-friendliness test, more people felt that Examples 11-12 were skin-friendly than Example 1, indicating that the antibacterial properties and skin-friendliness of the fabric can be improved by adding composite breathable fillers.

[0130] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. An antibacterial, soft and skin-friendly fabric, characterized in that: The raw materials comprising the following weight percentages are prepared: Modal fiber 60-65 parts Polylactic acid 30-35 parts 3-6 parts hydrophobic chitosan Coupling agent 1-3 parts Calcium carbonate powder 5-10 parts 2-5 parts of polyethylene wax; The hydrophobic chitosan is prepared by the following method: A: mixing the aromatic ketone with a water-insoluble organic solvent to obtain a mixed solution; B: Dissolve chitosan in acetic acid until the chitosan is dissolved, heat to 40-50°C, add the mixed solution, add an acid catalyst during stirring, continue stirring for 5-8 hours, then add sodium borohydride, stir for 1-2 hours to obtain a primary product; C: Place the primary product in 20-25°C water, stir, filter, obtain solid, rinse, and dry to obtain hydrophobic chitosan; The molar ratio of the aromatic ketone to chitosan is 1:(1.1-1.3); The acidic catalyst is hydrochloric acid or sulfuric acid; The method for preparing the antibacterial soft skin-friendly fabric comprises the following preparation steps: S1. According to parts by weight, polylactic acid, hydrophobic chitosan, calcium carbonate powder, coupling agent and polyethylene wax are first mixed, and put into a spinning box for spinning, the spinning temperature is 200-230°C, the spinning winding speed is 1000-2000m / min, and then drafted, the drafting temperature is 180-190°C, and the drafting speed is 1000-1500m / min to obtain polylactic acid fiber; S2. Blending the polylactic acid fiber with the modal fiber to obtain an antibacterial, soft and skin-friendly fabric.

2. The antibacterial soft skin-friendly fabric according to claim 1, characterized in that: The modal fiber needs to be pretreated before use, and the pretreatment steps are as follows: The modal fiber is immersed in a solution containing a hydrophobic organic silane coupling agent, taken out, and dried to obtain the pretreated modal fiber.

3. The antibacterial soft skin-friendly fabric according to claim 2, characterized in that: The hydrophobic silane coupling agent includes one of vinyl trimethoxy silane, phenyl trimethoxy silane, perfluoro silane or a linear silane with a carbon number greater than 15.

4. The antibacterial soft skin-friendly fabric according to claim 2, characterized in that: The mass fraction of the solution containing the hydrophobic organic silane coupling agent is 2-5%.

5. The antibacterial soft skin-friendly fabric according to claim 1, characterized in that: The weight average molecular weight of the polylactic acid is 70,000-150,000.

6. The antibacterial soft skin-friendly fabric according to claim 1, characterized in that: The antibacterial, soft and skin-friendly fabric also includes 4-8 parts by weight of a composite breathable filler, each part of which is obtained by mixing a nano-scale porous inorganic substance and a dispersant in a weight ratio of 5:(1-2).

Citation Information

Patent Citations

  • Method for preparing chitosan grafted polylactic acid in ionic liquid

    CN102329422A

  • Method for catalytically synthesizing 4,6-diaryl pyrimidine-2(1H)-one derivative by using sulfonic acid functional chitosan

    CN107266372A